George Short Movie's Search for Semiotic Aspects - Kharris Nur Qotimah (Cinematology: Journal Anthology of Film and Television Studies, 2021)
George's film tells of a tall man with a yellow hat named Ted who is assigned to get artifacts for museum needs, then Ted or better known as the yellow hat goes to Africa to get valuable artifacts that are useful for attracting many visitors to the museum where he works. On the way, he meets a brown monkey who is always curious about anything. The yellow hat named the monkey by the name of George and they became friends and lived in a hotel in the middle of the city. The purpose of this study was to determine the semiotic aspects contained in the cartoon film "George Short Movie" which is looking for some parts of the semiotic aspect which include index, icon, symbol. The method used in this research is a qualitative descriptive method. Qualitative descriptive method is a research method based on the philosophy of postpositivism which is used to research on a natural object condition, where the researcher is the key instrument of data collection techniques carried out by trigulation (combined), data analysis is inductive/qualitative, and qualitative research results emphasize more meaning rather than generalization. This qualitative descriptive research aims to describe, describe, explain, explain and answer in more detail about the problems to be studied by studying as much as possible the chosen subject. Data collection is carried out using digital communication tools in the form of cellphones so that the values contained in the George Short Movie can be seen in detail and clearly. The results of this study indicate that in this George Short film cartoon, there are insights, namely index, icon, symbol, as the meaning used to communicate the story visually.